A Possible Connection Between Plant Longevity and the Absence of Protein Fibrillation: Basis for Identifying Aggregation Inhibitors in Plants - Mohammad-Beigi, Hossein; Kjaer, Lars; Eskandari, Hoda; Aliakbari, Farhang; Christiansen, Gunna; Ruvo, Gianluca; Ward, Jane L.; Otzen, Daniel Erik (Frontiers in Plant Science, 2019)
The ability of proteins to aggregate to form well-organized beta-sheet rich amyloid fibrils is increasingly viewed as a general if regrettable property of the polypeptide chain. Aggregation leads to diseases such as amyloidosis and neurodegeneration in humans and various mammalian species but is also found in a functional variety in both animals and microbes. However, there are to our knowledge no reports of amyloid formation in plants. Plants are also the source of a large number of aggregation-inhibiting compounds. We reasoned that the two phenomena could be connected and that one of (many) preconditions for plant longevity is the ability to suppress unwanted protein aggregation. In support of this, we show that while protein extracts from the sugar maple tree A. saccharum fibrillate readily on their own, this process is efficiently abolished by addition of small molecule extracts from the same plant. Further analysis of 44 plants showed a correlation between plant longevity and ability to inhibit protein aggregation. Extracts from the best performing plant, the sugar maple, were subjected to chromatographic fractionation, leading to the identification of a large number of compounds, many of which were shown to inhibit aggregation in vitro. We suggest that it has been advantageous for plants to maintain an efficient collection of aggregation-inhibiting metabolites as long as they do not impair metabolite function; consequently, long-lived plants may be particularly appropriate sources of new anti-aggregation compounds with therapeutic potential.